2001
DOI: 10.1067/mhn.2001.118074
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Evaluation in Squamous Cell Carcinoma of the Head and Neck

Abstract: SLN evaluation in N0 neck in squamous cell carcinoma of the head and neck is accurately feasible and seems to adequately predict the presence of occult metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
1
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 10 publications
(26 reference statements)
6
85
1
8
Order By: Relevance
“…These results are comparable to the findings of other groups also applying radiological criteria for staging (Stoeckli et al, 2001;Barzan et al, 2002;Werner et al, 2002a). The better the staging methods are in detecting small metastases, the less occult metastases will be overlooked and the more valuable will be the impact of an additional sentinel lymph-node procedure.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results are comparable to the findings of other groups also applying radiological criteria for staging (Stoeckli et al, 2001;Barzan et al, 2002;Werner et al, 2002a). The better the staging methods are in detecting small metastases, the less occult metastases will be overlooked and the more valuable will be the impact of an additional sentinel lymph-node procedure.…”
Section: Discussionsupporting
confidence: 85%
“…Studies applying a radiolabelled tracer with or without additional blue dye, however, were promising. The majority of the studies reported results favouring the sentinel lymph-node concept (Koch et al, 1998;Shoaib et al, 1999Shoaib et al, , 2001Alex et al, 2000;Zitsch et al, 2000;Mozzillo et al, 2001;Stoeckli et al, 2001Stoeckli et al, , 2002Barzan et al, 2002;Werner et al, 2002a, b). Groups who worked with blue dye report of an extravasation of the blue dye into the tissue (Pitman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping is performed using preoperative lymphoscintigraphy and a g-counting probe (62). Imaging procedures are similar to those used for breast cancer and melanoma, including dynamic and planar imaging and skin marking.…”
Section: Head and Neck Malignanciesmentioning
confidence: 99%
“…Lymph nodes can often be adequately localized with planar imaging alone (62,63). However, the anatomic complexity of the head and neck and the proximity of some primary lesions to SLNs and other important structures suggest SPECT/CT should be included in some cases (64,65).…”
Section: Head and Neck Malignanciesmentioning
confidence: 99%